2018
DOI: 10.1021/acs.jpca.7b11853
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Interactions in Iminophosphorane Superbase Complexes with Carbon Dioxide

Abstract: Iminophosphoranes or phosphazenes are an important class of compounds with increasing use in synthetic organic chemistry as neutral organic superbases exhibiting low nucleophilicity. Their electronic structure and therefore their properties strongly depend on substitution, but there have been very few theoretical studies devoted to this topic, and more specifically to the formation of electron donor-acceptor complexes of iminophosphoranes with electrophiles. In this work, we have investigated the interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…There are numerous studies related with CO2 including in catalysis [25], processing polymers [26], engineering [27], absorption processes [28,29], crop development [30], fuels [31], lasers [32], and combustion research [33]. Also, the CO2 molecule has been the subject of investigation from the theoretical point of view [29,34,35]. Our previous studies concerning A•••B complexes with B being CO2 are reported in references [36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous studies related with CO2 including in catalysis [25], processing polymers [26], engineering [27], absorption processes [28,29], crop development [30], fuels [31], lasers [32], and combustion research [33]. Also, the CO2 molecule has been the subject of investigation from the theoretical point of view [29,34,35]. Our previous studies concerning A•••B complexes with B being CO2 are reported in references [36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…The usage of supercritical carbon dioxide (scCO 2 ) was early discovered with extensive applications in nanomaterials, chemical engineering, food science, and pharmaceuticals. , Besides the understanding of thermodynamic, kinetic, and critical properties of scCO 2 reactions, the solubility and intermolecular interactions involving scCO 2 are the research subfields that attract great scientific attention because of practical applications. Comprehensive insight into the interactions involving CO 2 at the molecular level has an important influence on improving technological applications based on scCO 2 . Numerous studies on complexes of organic molecules and CO 2 were conducted to unveil the nature of intermolecular interactions between these molecules. The >C/SO···C tetrel bond was addressed as the bonding feature of binary complexes formed by carbonyl/sulfoxide compounds and CO 2 . ,, This feature was also investigated for larger complexes with 2–3 CO 2 molecules. , …”
Section: Introductionmentioning
confidence: 99%